A fast self-cleaning SERS-active substrate based on an inorganic–organic hybrid nanobelt film. Issue 32 (27th July 2015) - Hao, Rui; Lin, Jie; Wang, Hua; Li, Bo; Li, Fengshi; Guo, Lin
Abstract : Ag@Ag(DMSO) x Cl nanobelts can achieve fast self-cleaning by the photodegradation of probe molecules during the in situ SERS detection process. Abstract : Surface-enhanced Raman scattering (SERS) spectroscopy, as a robust and attractive spectroscopic technique, has been widely used for the unequivocal identification of analytes, and an ideal SERS substrate that is highly sensitive and reproducible. Currently, existing substrates usually exhibit substantial sensitivity, however, achieve recyclable utilization through multi-step and complex procedures with the prerequisite of external facilities. Herein, an inorganic–organic hybrid nanobelt film assembled by novel Ag@Ag(DMSO) x Cl nanobelts was proposed as an active SERS substrate. This unique substrate exhibits highly sensitive SERS detection properties, and realizes ultrafast self-cleaning by in situ photocatalytic degradation of targeted molecules adsorbed onto the film during the detection process, showing the potential for real-time online monitoring. Our study demonstrates a new concept for preparing an in situ self-cleaning substrate by the rational design and assembly of special nanomaterials.